2017
DOI: 10.1186/s40168-017-0256-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of the gut microbiota in people sharing a confined environment, a 520-day ground-based space simulation, MARS500

Abstract: BackgroundThe intestinal microbial communities and their temporal dynamics are gaining increasing interest due to the significant implications for human health. Recent studies have shown the dynamic behavior of the gut microbiota in free-living, healthy persons. To date, it is not known whether these dynamics are applicable during prolonged life sharing in a confined and controlled environment.ResultsThe MARS500 project, the longest ground-based space simulation ever, provided us with a unique opportunity to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 39 publications
9
98
0
Order By: Relevance
“…Hence, one of the major challenges in manned space exploration is protecting astronauts from microbiota dysbiosis. In recent years, with the development of high-throughput sequencing technology for complex microbial communities, both hostderived and environmental microbiome have frequently been studied, either in space stations (Checinska et al, 2015;Moissleichinger et al, 2016;Mora et al, 2016b;Be et al, 2017) or ground-based space simulations Mayer et al, 2016;Sun et al, 2016;Blachowicz et al, 2017;Schwendner et al, 2017;Turroni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, one of the major challenges in manned space exploration is protecting astronauts from microbiota dysbiosis. In recent years, with the development of high-throughput sequencing technology for complex microbial communities, both hostderived and environmental microbiome have frequently been studied, either in space stations (Checinska et al, 2015;Moissleichinger et al, 2016;Mora et al, 2016b;Be et al, 2017) or ground-based space simulations Mayer et al, 2016;Sun et al, 2016;Blachowicz et al, 2017;Schwendner et al, 2017;Turroni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…4A ). If the stool proteins were to match previous microbiome results, we would expect to see temporal variability unique to each individual in unperturbed, uncontrolled diet conditions (14, 20). The resulting principle component analysis (PCA) with Bray Curtis distance metric indicated that each subjects’ stool proteins varied temporally to different extents, confirming that stool protein temporal variability mirrors previously described temporal microbiome variability.…”
Section: Resultsmentioning
confidence: 95%
“…The same evidence indicates that crewmembers, though sharing the same environment, did not exchange their salivary microbiota, leading to hypothesize that quite stable personal salivary microbiota features are present in humans and confirming the between-subject effect. The fecal microbiota of the same crewmembers showed an increasing trend of similarity among subjects, especially in relation to a sharing of rare taxa, 17 indicating that salivary microbiota has a more pronounced personalization than fecal microbiota. Indeed, from our data there are no evidences of an ecological successions, as those shown in the fecal microbiota of the same crewmembers.…”
Section: Discussionmentioning
confidence: 97%
“…Data from Mars500 experiment were studied from various point of view, including behavior, 11 effect of cultural background, 12 cognitive performances, 13 circadian rithms, 14 hormone levels, 15 and surface and gut microbiota. 16,17 Mars500 hence constitutes a unique experiment to determine, in a longitudinal study design, the composition and importance of the resident microbiota vs. a more variable microbiota (changing with time and environmental conditions) in humans. Aim of the work was indeed to inspect the temporal dynamics of salivary microbiota, assessing the effect of diet regimes and individuality, using Mars500 as a unique long-term experiment where subjects were all confined in the same shared environment.…”
Section: Introductionmentioning
confidence: 99%